2018
DOI: 10.1007/s00330-018-5624-7
|View full text |Cite
|
Sign up to set email alerts
|

The role of wall shear stress in the parent artery as an independent variable in the formation status of anterior communicating artery aneurysms

Abstract: • Multivariate analyses and a two-piecewise linear regression model were used to evaluate the risk factors for AcomA aneurysm formation and the threshold effect of WSS on AcomA aneurysm formation. • WSS ranging between 7.8 and 12.3 dyne/cm was shown to be a reliable hemodynamic parameter in the formation of AcomA aneurysms. The probability of AcomA aneurysm formation increased one-fold for each additional unit of WSS. • An ultrasound-based TCCD technique is a simple and accessible noninvasive method for detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 37 publications
1
25
0
Order By: Relevance
“…We compared Figures 1, 2 and found out that high infiltration regions were associated with excessively low wall shear stress regions, which is consistent with literature studies that low shear stress was associated with atherosclerotic change in the aneurysm wall (23)(24)(25)(26). Though aneurysm initiation is generally considered to be linked with high shear stress (27,28), the role of wall shear stress in aneurysm rupture remains controversial. In some studies, the rupture sites of aneurysms were found to be associated with the low shear stress region (29,30).…”
Section: Discussionsupporting
confidence: 84%
“…We compared Figures 1, 2 and found out that high infiltration regions were associated with excessively low wall shear stress regions, which is consistent with literature studies that low shear stress was associated with atherosclerotic change in the aneurysm wall (23)(24)(25)(26). Though aneurysm initiation is generally considered to be linked with high shear stress (27,28), the role of wall shear stress in aneurysm rupture remains controversial. In some studies, the rupture sites of aneurysms were found to be associated with the low shear stress region (29,30).…”
Section: Discussionsupporting
confidence: 84%
“…Current hypotheses of IA genesis are based on the chronic vascular injury as a result of long-lasting hemodynamic stress with subsequent inflammatory cascades resulting in degeneration and reorganization of the affected arterial wall (8,13,21). In addition, role of parent artery morphology in development of IA was also previously discussed (14,26).…”
Section: Introductionmentioning
confidence: 99%
“…The normal TAWSS magnitudes in arteries range from 1.5 to 7 Pa, whereas it could reach 1 to 22 Pa in IAs [58]. Despite both aberrantly high (>7 Pa) [38][39][40][41] and low TAWSS (<1.5 Pa) [27,[34][35][36][37], they have been reported to contribute to the IA rupture via complex mechanobiological mechanisms [14,17]; associations between low TAWSS and the risk of rupture of large IAs (>5 mm) have been identified by some of the latest investigations [14,15,59]. Additionally, high OSI (>0.2), which reflects the elevated local flow instability, was also considered as an important factor in the rupture of IAs by upregulating inflammatory cell-mediated destructive remodeling [14,56,[60][61][62].…”
Section: Impacts Of Unilateral Ica Revascularization On Acoaa Hemodynmentioning
confidence: 96%
“…The decreasing stenosis degree resulted in a reduction of overall TAWSS level and maximum TAWSS on the dome of the ACoAA. Table 3 listed the low TAWSS (<1.5 Pa) [27,[34][35][36][37] and high TAWSS (>7 Pa) [38][39][40][41] areas on the ACoAA dome. Compared with the sever stenosis case, a larger low TAWSS area and smaller high TAWSS area were observed in the case of reduced stenosis degree.…”
Section: The Impact Of Revascularization On Flow Patternsmentioning
confidence: 99%